2014
DOI: 10.1177/1329878x1415000114
|View full text |Cite
|
Sign up to set email alerts
|

Women's Pages in Australian Print Media from the 1850s

Abstract: For a roughly a century, from the 1870s to the 1970s, most Australian newspapers ran a section directed towards a woman reader written from a woman's perspective and edited by a female journalist. The rise and fall of the women's editor's ‘empire within an empire’ provides insight into female journalists' industrial situation, as well as a window on to gender relations in colonial and post-Federation Australia. This history matches wider struggles over the notion of separate spheres and resulting claims for eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Women’s entry into press photography was influenced by their employment in the media more widely and through participation in the growing field of commercial photography. First, women had worked as journalists since the 19th century, although their output was generally constricted to writing from a ‘woman’s perspective’ on dedicated women’s pages (Baker, 2015b; Lloyd, 2014; Lemon, 2008a). Opportunities for women in general reporting slowly expanded, particularly during World War II (Baker, 2015a; Clarke, 2014: 496), but it was only in the 1960s that their numbers grew significantly and reporting became more diverse.…”
Section: Women Press Photographersmentioning
confidence: 99%
“…Women’s entry into press photography was influenced by their employment in the media more widely and through participation in the growing field of commercial photography. First, women had worked as journalists since the 19th century, although their output was generally constricted to writing from a ‘woman’s perspective’ on dedicated women’s pages (Baker, 2015b; Lloyd, 2014; Lemon, 2008a). Opportunities for women in general reporting slowly expanded, particularly during World War II (Baker, 2015a; Clarke, 2014: 496), but it was only in the 1960s that their numbers grew significantly and reporting became more diverse.…”
Section: Women Press Photographersmentioning
confidence: 99%
“…As one of us has argued previously in Media International Australia (Lloyd, 2014), the situation of women journalists in print can be traced through debates over the scope of the ‘women’s page’ in commercial daily newspapers. The rise and fall of the women’s page as a media ‘empire within an empire’ provides insight into female journalists’ industrial situation up to and including the second wave (Lloyd, 2014).…”
Section: Women’s Labour In Media Industriesmentioning
confidence: 99%
“…As one of us has argued previously in Media International Australia (Lloyd, 2014), the situation of women journalists in print can be traced through debates over the scope of the ‘women’s page’ in commercial daily newspapers. The rise and fall of the women’s page as a media ‘empire within an empire’ provides insight into female journalists’ industrial situation up to and including the second wave (Lloyd, 2014). Furthermore, US-based feminist media historians have explored the rich vein of gendered news agendas, by documenting the career histories of individual journalists (Yang, 1996) and the negotiations by media employees themselves of transitions away from a dedicated women’s page in newspapers (Harp, 2006).…”
Section: Women’s Labour In Media Industriesmentioning
confidence: 99%
See 1 more Smart Citation
“…This changed once women were identified as a separate readership. The Australian Women’s Weekly opened up a slightly wider range of employment for women journalists from its first publication in 1933 (Clarke, 2014: 496), but, for the large part, the ‘women’s pages’ dominated, taking the form of special interest sections outside the flow of news events and relegated to the back of the paper (Lloyd, 2014: 61). Although their establishment demonstrated that newspaper proprietors and editors were at least acknowledging their women readers, women journalists became confined to working on them, trapped in ‘a world of intimate, chatty escapism, varnished with a layer of social snobbery’ (Pearce, 1998: 144).…”
Section: Skirting the Women’s Pagesmentioning
confidence: 99%